2012
DOI: 10.4161/cam.21294
|View full text |Cite
|
Sign up to set email alerts
|

The malignant social network

Abstract: Tumors contain a vastly complicated cellular network that relies on local communication to execute malignant programs. The molecular cues that are involved in cell-cell adhesion orchestrate large-scale tumor behaviors such as proliferation and invasion. We have recently begun to appreciate that many tumors contain a high degree of cellular heterogeneity and are organized in a cellular hierarchy, with a cancer stem cell (CSC) population identified at the apex in multiple cancer types. CSCs reside in unique micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 146 publications
0
17
0
Order By: Relevance
“…The traditional two-dimensional (2D) cell culture systems are adequate to study cancer cells in vitro , but cannot completely simulate the in vivo cellular environment. This important difference in the cellular surroundings [9] may influence CSC properties and prevent their differentiation [10].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional two-dimensional (2D) cell culture systems are adequate to study cancer cells in vitro , but cannot completely simulate the in vivo cellular environment. This important difference in the cellular surroundings [9] may influence CSC properties and prevent their differentiation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Cell density is closely dependent on cell adhesion and cell-to-cell communication. Our group and many other researchers have previously outlined the importance of adhesion and cell communication molecules in CSC maintenance and expansion (20,(68)(69)(70)(71). However, in an experimental setting, cell density is often overlooked and poorly controlled for across studies in CSC field.…”
Section: Discussionmentioning
confidence: 99%
“…This was more apparent in CSCs and vascular niches. As previous studies have reported that CSCs or vascular niches may be the base for metastasis and network-like information export and exchange ( 15 , 49 , 50 ), it was hypothesized that cellular communication would be more strongly observed near these niches in vivo . However, the transmission of information to the distant areas of the tissues may still need to occur through microtubule-like channels, cell-associated cords or tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%